Identification, Expression, and Functional Analysis of the Group IId WRKY Subfamily in Upland Cotton (Gossypium hirsutum L.) - Gu, Lijiao; Wang, Hantao; Wei, Hengling; Sun, Huiru; Li, Libei; Chen, Pengyun; Elasad, Mohammed; Su, Zhengzheng; Zhang, Chi; Ma, Liang; Wang, Congcong; Yu, Shuxun (Frontiers in Plant Science, 2018)
WRKY transcription factors have diverse functions in regulating stress response, leaf senescence, and plant growth and development. However, knowledge of the group IId WRKY subfamily in cotton is largely absent. This study identified 34 group IId WRKY genes in the Gossypium hirsutum genome, and their genomic loci were investigated. Members clustered together in the phylogenetic tree had similar motif compositions and gene structural features, revealing similarity and conservation within group IId WRKY genes. During the evolutionary process, 14 duplicated genes appeared to undergo purification selection. Public RNA-seq data were used to examine the expression patterns of group IId WRKY genes in various tissues and under drought and salt stress conditions. Ten highly expressed genes were identified, and the ten candidate genes revealed distinct expression patterns under drought and salt treatments by qRT-PCR analysis. Among them, Gh_A11G1801 was used for functional characterization. GUS activity was differentially induced by various stresses in Gh_A11G1801p::GUS transgenic Arabidopsis plants. The virus-induced gene silencing (VIGS) of Gh_A11G1801 resulted in drought sensitivity in cotton plants, which was accompanied by elevated malondialdehyde (MDA) content and reduced catalase (CAT) content. Taken together, these findings obtained in this study provide valuable resources for further studying group IId WRKY genes in cotton. Our results also enrich the gene resources for the genetic improvements of cotton varieties that are suitable for growth in stressful conditions.